Empowering Family to Manage Fatigue using Back Massage - Bambang Aditya Nugraha; Gusgus Ghraha Ramdhanie; Sulastini Sulastini (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The Postoperative phase is a critical period in the recovery of surgical patients. During this phase, many patients experience fatigue. Postoperative fatigue is challenging and affects quality of life. Back massage is a complementary therapy performed to manage fatigue and reduce muscle tension. For this reason, a family empowering program was conducted in one of the surgical wards in one of the government hospitals in Sumedang, which was attended by 10 participants consisting of patient families. Program participants are families of patients undergoing surgery. Based on the records obtained, the patient's family experienced an increase in knowledge measured through pre-test and post-test. At the pre-test stage, the percentage of participants who had poor knowledge was 50% and after participating in the program decreased to 30%. Meanwhile, the percentage at the good knowledge level at the pre-test was 20% and at the post-test there was an increase to 40%. Based on this percentage, it was found that there was an increase in participants' knowledge before and after the program related to the implementation of foot massage in order to manage fatigue. Back massage is recommended to be presented as an option in developing fatigue management strategies in postoperative patients.